Socio-economic assessment of dog population management systems: a scoping review - Ghimire, Rabina; Mohanty, Parimala; Hiby, Elly; Larkins, Andrew; Dürr, Salome; Hartnack, Sonja (Frontiers in Veterinary Science, 2025)
IntroductionDog Population Management (DPM) systems primarily aim to reduce the free-roaming dog population, improve the health and welfare of humans and dogs, and foster their peaceful coexistence. A key challenge to resource allocation and evidence-based policy making in DPM is the rare evaluation of the associated socio-economic impacts. This scoping review identifies, maps, and summarizes published parameters and methods on the socio-economic aspect of DPM systems.MethodsFollowing PRISMA-ScR guidelines, and with a protocol registered on the Open Science Framework, this review explores (i) types of DPM services, (ii) types of parameters (intervention, impact, monetized, or non-monetized), (iii) methodological approaches (such as cost–benefit or cost-effectiveness analysis), and (iv) gaps and challenges in socio-economic DPM assessments. Relevant publications were identified through a systematic search of PubMed, Embase, Scopus, and Web of Science.ResultsOur review identified 14 out of more than 7,200 studies indicating the limitation of socio-economic data associated with DPM systems. The studies revealed diverse approaches to DPM, sterilization being the most frequently used service, often combined with vaccination and community awareness. Culling was also used by several studies as a DPM intervention, though considered unethical. The review highlighted a range of intervention, impact, and monetary parameters to evaluate the economics of DPM systems, demonstrating the complexity and varied scope of the services. Varied categorizations of the dog population were observed, making comparative evaluation challenging. Economic methods such as cost–benefit and cost-effectiveness analyses were observed, identifying several associated economic metrics. Studies highlighted gaps mostly related to data availability and accessibility.ConclusionThe limitations of socio-economic data arise from a lack of standardized methodologies across regions and contexts and limited data collection efforts. Prioritizing systematic collection of data on costs, benefits and social impacts allows for a more robust analysis of DPM systems. Developing tools and standardized reporting methods would further facilitate consistent evaluation of impacts, efficient resource allocation and evidence-based policy making to implement the most cost-effective DPM systems.Systematic review registrationDOI: 10.17605/OSF.IO/NHE3X